2019
DOI: 10.1186/s13046-019-1049-7
|View full text |Cite
|
Sign up to set email alerts
|

CD36 mediates palmitate acid-induced metastasis of gastric cancer via AKT/GSK-3β/β-catenin pathway

Abstract: BackgroundGastric cancer (GC) has a clear predilection for metastasis toward the omentum which is primarily composed of adipose tissue, indicating that fatty acids may contribute to this phenomenon. However their function remains poorly understood in GC. In this study, we investigated the role of palmitate acid (PA) and its cellular receptor CD36 in the progression of GC.MethodsImmunohistochemical (IHC) staining was performed to detect CD36 expression in GC tissues and its clinical significance was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(159 citation statements)
references
References 38 publications
7
152
0
Order By: Relevance
“…Exogenous treatment of FABP4 increased Akt and MAPK signaling. The increased expression of the FA transporter CD36 in gastric cancer tissues also correlated with poor prognosis in patients [121]. CD36 mediates the palmitate acid-induced metastasis of GC via Akt.…”
Section: Lipid Metabolismmentioning
confidence: 88%
“…Exogenous treatment of FABP4 increased Akt and MAPK signaling. The increased expression of the FA transporter CD36 in gastric cancer tissues also correlated with poor prognosis in patients [121]. CD36 mediates the palmitate acid-induced metastasis of GC via Akt.…”
Section: Lipid Metabolismmentioning
confidence: 88%
“…Hua et al reported that knockdown of ANXA11 suppressed gastric cancer cell proliferation, invasion and migration through the AKT/GSK-3β pathway, which was acted as a prognostic factor and promising molecular target for gastric cancer treatment [31]. Pan et al demonstrated that CD36 regulated palpitate acid-induced metastasis in gastric cancer by AKT/GSK-3β/βcatenin pathway, acting as a potential molecular target for clinical intervention [32]. In our study, we found that miR-450 blocked the AKT/GSK-3β signaling pathway to regulate the progression of gastric cancer and miR-450 levels were related with strength of the AKT/GSK-3β signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CD36 serves as the surface receptor for palmitate uptake and plays a critical role in palmitate-induced signaling pathways. It has been shown that increased CD36 expression in gastric cancer is correlated with poor prognosis [82]; accordingly, palmitate promotes gastric cancer metastasis in a CD36-dependent manner [83]. Palmitate stimulation increases monocytic CD36 expression, macrophage differentiation, and proinflammatory cytokine production [84].…”
Section: Involvement Of Palmitate In Immune-related Cell Interactionsmentioning
confidence: 99%
“…Since CD36 serves as the major transporter for cell palmitate uptake, the targeting of palmitate-mediated signaling has emerged as a potential therapeutic tactic. Indeed, palmitate-induced metastasis of gastric cancer is dependent on CD36, and high CD36 expression levels in gastric cancer patients correlate with poor clinical outcome; therefore, there is a possibility that blocking of the CD36-palmitate axis may serve as a potential gastric cancer treatment [83]. Indeed, CD36 deletion in a prostate cancer animal model revealed a dramatic decrease in fatty acid uptake and ameliorated cancer progression [86].…”
Section: Targeting Of Palmitate-induced Pathways As a Therapeutic Strmentioning
confidence: 99%